The Conceptual Metaphors and Frames of Happiness in Kimiya al-Sa‘adah: A Cognitive-Linguistic Study - Nur Khofifah Saadiah; Sailal Arimi (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
The study examines the conceptual metaphors and frames found in a work by Imam al-Ghazali, Kimiya al-Sa‘adah. The analysis employs Conceptual Metaphor Theory (CMT) and frame analysis, using a qualitative descriptive method. The purpose of this study is to identify the conceptualization of “happiness” in the Islamic classical text and to contribute to cognitive linguistics. Based on the findings, the study identifies at least eight conceptual metaphors: HAPPINESS IS PURIFICATION, HAPPINESS IS CLOSENESS TO GOD, HAPPINESS IS SPIRITUAL GROWTH, HAPPINESS IS DEVOTIONAL INTIMACY, HAPPINESS IS DIVINE LOVE THAT GROWS, HAPPINESS IS REUNITING WITH GOD, HAPPINESS IS SELF-DISCIPLINE, and HAPPINESS IS AN ETERNAL SPIRITUAL JOURNEY. These conceptual metaphors form four frames through their underlying cognitive structures: self-purification, divine proximity, spiritual ascent, and eschatological reunion. From these findings, the researchers conclude that Imam al-Ghazali does not define happiness as worldly pleasure alone, but as the culmination of spiritual purification that leads a person back to God.